Examining the Relationship Between Personality Traits and Exposure to Workplace Bullying. Issue 4 (August 2019) - Rai, Arpana; Agarwal, Upasna A.
Abstract: Workplace bullying is a common and constantly occurring phenomenon in organizations. Various factors render a workplace conducive to the occurrence of bullying-like features of the work environment and personality traits of the employees. While work environment features are well-established antecedents of workplace bullying, much of the research on personality traits as antecedents of bullying remains inconclusive. Drawing on the victim precipitation theory and the Big Five personality taxonomy, the present study aims to examine the relationship between four personality traits (conscientiousness, agreeableness, extraversion and openness to experience) and exposure to workplace bullying. We have excluded neuroticism, as it is a well-established antecedent of workplace bullying, whereas literature suggests mixed findings on the relationships between the remaining four personality traits and workplace bullying. A total of 835 full-time Indian managers working across different Indian organizations served as the sample for our study. The results suggest that conscientiousness, agreeableness, extraversion and openness to experience negatively correlate with workplace bullying. Implications for theory and practice are also discussed in this article.